KASUS PENCEMARAN NAMA BAIK LUHUT BINSAR PANJAITAN BERDASARKAN PERSPEKTIF SEMIOTIKA LAGU “ANGGURMAN” - Fadli, Hasan; Zusyana Dewi, Ratnaningrum; Ningsih, Masnia (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2024)
Freedom of speech is one of the most protected human rights. However, in the process it turned out that there were still violations of freedom of expression, especially during the New Order government. Many activists and artists were born who opposed the authoritarian attitude of the New Order through their works. After the fall of the New Order, the Reformation returned to Indonesia's right to freedom of speech. After several years, there have been threats regarding violations of the right to freedom of expression with the emergence of the